Break It Down: A Comparison of Macro- and Microtasks - Cheng, Justin; Teevan, Jaime; Iqbal, Shamsi; Bernstein, Michael S. (ACM Conference on Human Factors for Computing Systems (CHI), 2015)
A large, seemingly overwhelming task can sometimes be transformed into a set of smaller, more manageable microtasks that can each be accomplished independently. For example, it may be hard to subjectively rank a large set of photographs, but easy to sort them in spare moments by making many pairwise comparisons. In crowdsourcing systems, microtasking enables unskilled workers with limited commitment to work together to complete tasks they would not be able to do individually. We explore the costs and benefits of decomposing macrotasks into microtasks for three task categories: arithmetic, sorting, and transcription. We find that breaking these tasks into microtasks results in longer overall task completion times, but higher quality outcomes and a better experience that may be more resilient to interruptions. These results suggest that microtasks can help people complete high quality work in interruption-driven environments.